2018
DOI: 10.1111/ceo.13408
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year reinvestigation of ocular manifestations in Marfan syndrome

Abstract: Importance: Long-term follow-up of Marfan syndrome (MFS) patients. Background: Investigate changes in ocular features in MFS patients fulfilling the Ghent-2 criteria following a period of 10 years. Design: Repeated cross-sectional study with two observations. Participants: Eighty-four MFS patients were investigated in 2003-2004 (baseline). Forty-four of these patients (52%) were examined after 10 years. Methods: A comprehensive ocular examination performed at baseline and follow-up. Main Outcome Measures: Deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 42 publications
1
20
1
Order By: Relevance
“…Ectopia lentis is usually seen from childhood, but it can also progress in adults. 27 , 28 It often requires surgical treatment, and since the zonules are weakened, suture-fixated MCTR is usually recommended, if possible to retain the lens capsule for in-the-bag IOL placement. 20 In the eyes of the Marfan patients in our study, the suture breakage rate was 42%.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopia lentis is usually seen from childhood, but it can also progress in adults. 27 , 28 It often requires surgical treatment, and since the zonules are weakened, suture-fixated MCTR is usually recommended, if possible to retain the lens capsule for in-the-bag IOL placement. 20 In the eyes of the Marfan patients in our study, the suture breakage rate was 42%.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusions should be viewed with caution for other ethnic populations. Third, adult patients were excluded from the current study, as AL were shown to be stable in adults (> 30 years old) with MFS during a 10-year follow up 37 . The cross-sectional nature of our study also limited our ability to track changes in AL data over time.…”
Section: Discussionmentioning
confidence: 99%
“…The main organ systems affected are the cardiovascular, skeletal and ocular systems. Ocular findings include myopia, ectopia lentis, retinal detachment, glaucoma and early cataracts 77,78 . Ectopia lentis is the primary ocular complication of Marfan syndrome and occurs in approximately 60% of cases 77 .…”
Section: Cataract and Syndromesmentioning
confidence: 99%
“…Ocular findings include myopia, ectopia lentis, retinal detachment, glaucoma and early cataracts. 77,78 Ectopia lentis is the primary ocular complication of Marfan syndrome and occurs in approximately 60% of cases. 77 Though the overall prevalence of cataracts is not higher in Marfan syndrome, they tend to present at a younger age.…”
Section: Marfan Syndromementioning
confidence: 99%